Composite electrode material and preparation method and application thereof
By depositing different active components in situ on the surface of the foam current collector multiple times and building a multi-stage structure, the problem of poor cycling stability of multiphase metal compound composite materials in supercapacitor electrode materials is solved, and high specific capacitance and excellent Conductivity and good cycling performance, suitable for electrochemical energy storage systems with high energy density and long cycle life.
Patent Information
- Application Number
- CN202411568798.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
When existing multiphase metal compound composite materials are used as supercapacitor electrode materials, their cycle stability is poor, which limits their application in the field of energy storage.
By depositing different active components (manganese tetraoxide, nickel sulfide, zinc sulfide, nickel sulfide and manganese sulfide) in situ on the surface of the foam current collector, the rough surface and multi-stage structure are constructed to achieve the active substance and the foam current collector. Close contact provides a good 3D conductive network for electronic transmission.
It achieves high specific capacitance value, excellent conductivity and good cycling performance, provides high specific capacitance value and good cycling stability, and builds an electrochemical energy storage system with high energy density and long cycle life.
Smart Images

Figure CN119400601A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite electrode material and a preparation method and application thereof, belonging to the technical field of electrode materials. Background Art
[0002] Supercapacitors, also known as electrochemical supercapacitors, are advanced energy storage devices that use electrochemical reaction mechanisms to convert electrical energy into chemical energy and store charge. Thanks to their high energy storage capacity, fast charging characteristics, high power density, and long cycle life, supercapacitors are expected to become a core component of future energy storage systems. Electrode materials, as a medium for charge storage, play a vital role in the energy storage performance of supercapacitors. Therefore, the design and development of high-performance electrode materials is the main challenge currently faced by researchers.
[0003] In this field, AMPatil et al. prepared NiS nanosheets by hydrothermal method, which can provide a specific capacitance value of 880F / g at a scan rate of 5mV / s. After 4000 cycles, the capacitance retention rate is as high as 90%. Ting-Feng Yi et al. synthesized ZnS nanoparticles using hydrothermal technology and anion exchange reaction. The material exhibited superior electrochemical properties and had a maximum reversible specific capacitance of 824F / g at 1A / g. In addition, Bin Li et al. synthesized an ultrafine Mn by hydrothermal method. 3 O 4 The material exhibited a good specific capacitance value (401F / g) at a scan rate of 10mV / s.
[0004] Among many electrode materials, Ni-based, Mn-based, and Zn-based compounds have the advantages of high theoretical specific capacitance, abundant resources, pseudocapacitive properties with multiple oxidation states, and simple preparation process, and are considered to be very promising electrode active materials. However, these single metal compounds have problems such as low intrinsic conductivity and volume expansion during charging and discharging in practical applications, which seriously limit their specific capacitance and cycle stability, resulting in low power density and cycle life, thus hindering their large-scale application.
[0005] In recent years, people have prepared and studied the application potential of various multiphase metal compound composites in the field of supercapacitors. Specifically, Ali Asghar et al. synthesized NiS / ZnS composites by surfactant-driven hydrothermal method. The materials have a high conductivity at 0.5 mA / cm 2 The discharge time at the current density is as long as 461.97s (specific capacitance 461.97mF / cm 2), which is much longer than the discharge time of single NiS and ZnS electrodes under the same conditions (396.36s and 186.26s, respectively). Sreenivasa Kumar Godlaveeti et al. synthesized NiS / ZnO composites by hydrothermal method and found that when the ratio of NiS to ZnO in the composite material was 5:5, the composite material exhibited excellent specific capacitance characteristics (specific capacitance value was as high as 1322F / g at a current density of 1A / g) and good cycle life (specific capacitance retention rate was 76.66% after 1000 charge and discharge cycles). In addition, Qiang Hu et al. designed and synthesized MnO based on a simple solution method. 2 / Co 9 S 8 Layered core-shell nanostructures. The composite material is 2 The high specific capacitance of 643.3C / g is shown at the current density, which is the highest value for single MnO 2 10.1 times of that.
[0006] Therefore, the construction of multiphase metal compound composites has shown great application potential in improving the energy density and cycle stability of supercapacitors. However, current research results are still difficult to meet the current energy storage needs, and the overall electrochemical performance of electrode materials (such as specific capacitance and cycle stability) still has huge room for improvement. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a composite electrode material, which can solve the problem of poor cycle stability of the currently prepared multi-phase metal compound composite materials when used as supercapacitor electrode materials.
[0008] The second object of the present invention is to provide a composite electrode material that can solve the problem of poor cycle stability when the current multi-phase metal compound composite material is used as a supercapacitor electrode material.
[0009] The third object of the present invention is to provide an application of a composite electrode material, which can solve the problem of poor cycle stability when using multi-phase metal compound composite materials as supercapacitor electrode materials.
[0010] In order to achieve the above objectives, the technical solution adopted by the method for preparing the composite electrode material of the present invention is:
[0011] A method for preparing a composite electrode material comprises the following steps: immersing a foam current collector in a first reaction solution for a first heat preservation reaction and then placing the foam current collector in an alkali metal sulfide solution for a second heat preservation reaction to obtain a foam current collector loaded with active components, and then immersing the foam current collector loaded with the active components in a second reaction solution for reaction to obtain a composite electrode material; the first reaction solution is composed of nickel salt, zinc salt, manganese salt, ammonium fluoride, urea and water, and the second reaction solution is composed of nickel salt, manganese salt, thioacetamide and water.
[0012] The preparation method of the composite electrode material of the present invention comprises the following steps: firstly, a 3D network array of micronized sheets of nickel-zinc-manganese carbonate compounds is in situ grown on a foam current collector, and then a 3D network array of nanosheets composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide is obtained by ion exchange treatment, and finally, an amorphous thin sheet outer layer composed of manganese tetraoxide and nickel sulfide is deposited on the surface of the above-obtained 3D network array by a wet chemical method. The raw materials used in the composite material of the present invention are abundant in source and low in price; the preparation method is simple, and is conducive to low-cost large-scale production.
[0013] The preparation method of the composite electrode material of the present invention is simple to operate, environmentally friendly and reliable, and the raw materials are widely available and low in cost. In addition, the method significantly simplifies the process flow, shortens the electrode preparation time, and provides strong support for industrial production. The preparation method of the composite electrode material of the present invention can construct a rough surface and a multi-level structure on the surface of the foam current collector by repeatedly depositing different active components (manganese tetraoxide, nickel sulfide, zinc sulfide, nickel sulfide and manganese sulfide) on the surface of the foam current collector in situ. Since all active components can participate in the electrochemical energy storage reaction, rich redox reaction sites can be provided. The rough surface also provides more active sites for the electrochemical reaction, realizes the close contact between the active substance and the foam current collector, and provides a good 3D conductive network for electron transmission. Electrochemical performance tests show that the composite electrode material of the present invention not only has a high specific capacitance value, but also exhibits excellent conductivity and cycle performance, and is a very potential supercapacitor electrode material.
[0014] Preferably, the concentration of nickel salt in the first reaction solution is 0.05-0.1 mol / L, and the molar ratio of nickel element in nickel salt, zinc element in zinc salt, manganese element in manganese salt, ammonium fluoride and urea is 2:(1-1.05):(1-2):(4-4.05):(4-6).
[0015] Preferably, the first step of heat preservation reaction is carried out at a temperature of 120 to 125° C. for 6 to 8 hours.
[0016] Preferably, the concentration of the alkali metal sulfide solution is 0.1-0.2 mol / L.
[0017] Preferably, the temperature of the second step insulation reaction is 130-150° C. and the time is 7-8 hours.
[0018] Preferably, the concentration of thioacetamide in the second reaction solution is 0.05-0.1 mol / L, and the molar ratio of nickel element in nickel salt, manganese element in manganese salt and thioacetamide is 3:(1-1.05):(18-20).
[0019] Preferably, the foam current collector loaded with active components is immersed in the second reaction liquid for reaction at a temperature of 100 to 110° C. and a time of 2 to 3 hours.
[0020] Preferably, the nickel salt in the first reaction solution is nickel chloride, the zinc salt is zinc acetate, and the manganese salt is manganese sulfate; the nickel salt in the second reaction solution is nickel acetate, and the manganese salt is manganese acetate; the foam collector is foam nickel; the concentration of the nickel salt in the first reaction solution is 0.05 mol / L; the temperature of the first insulation reaction is 120°C; the foam collector loaded with active components is immersed in the second reaction solution for 2 hours for reaction; in the first reaction solution, the molar ratio of nickel in the nickel salt, zinc in the zinc salt, manganese in the manganese salt, ammonium fluoride and urea is 2:1:(1-2):4:(4-6); in the second reaction solution, the molar ratio of nickel in the nickel salt, manganese in the manganese salt and thioacetamide is 3:1:(18-20).
[0021] The technical solution adopted by the composite electrode material of the present invention is:
[0022] A composite electrode material prepared by the method for preparing the composite electrode material as described above.
[0023] The composite electrode material of the present invention can construct a rough surface and a multi-level structure on the surface of the foam current collector by sequentially loading different active components (manganese tetraoxide, nickel sulfide, zinc sulfide, nickel sulfide and manganese sulfide) on the surface of the foam current collector. All active components can participate in the electrochemical energy storage reaction. The rough surface and the multi-level structure also provide more active sites for the electrochemical reaction, realize the close contact between the active substance and the foam current collector, and provide a good 3D conductive network for electron transmission. Electrochemical performance tests show that the composite electrode material of the present invention not only has a high specific capacitance value, but also exhibits excellent conductivity and cycle performance, and is a highly potential supercapacitor electrode material. When the composite electrode material of the present invention is used as a supercapacitor electrode, it can provide a high specific capacitance value and good cycle stability, and the constructed electrochemical energy storage system has a high energy density and good cycle stability.
[0024] The composite electrode material of the present invention comprises a foam current collector and a multi-level hierarchical structure metal compound grown in situ on its surface. The inner layer of the hierarchical structure is composed of an interconnected 3D network array constructed by 2D nanosheets, and the outer layer is composed of interconnected amorphous sheets. Such a hierarchical structure can effectively improve the infiltration of the electrolyte and buffer the volume effect during the charging and discharging process, thereby ensuring the structural stability of the material. The surface morphology of the composite material is rough, which can provide more active sites for electrochemical reactions. The composite material is composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide. During the charging and discharging process, there are not only double-layer adsorption characteristics, but also Faraday cell-type redox reactions provided by metal atoms, and all active components can participate in the electrochemical energy storage reaction, thereby greatly improving the electrochemical performance of the composite electrode material, and facilitating the acquisition of an electrochemical energy storage system with high specific capacitance, long cycle life, low resistance and low cost.
[0025] The technical solution adopted by the application of the composite electrode material of the present invention as a supercapacitor electrode material is:
[0026] An application of the composite electrode material as described above as a supercapacitor electrode material.
[0027] When the composite electrode material of the present invention is used as a supercapacitor electrode material, it can provide a higher specific capacitance value and good cycle stability. The constructed electrochemical energy storage system has a higher energy density and good cycle stability.
[0028] The present invention achieves close contact between the active material and the foam current collector by repeatedly in-situ depositing different active components (manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide) on the surface of the foam current collector, providing a good 3D conductive network for electron transmission; the composite electrode material does not require any binder and conductive additive and can be directly used as an electrode, which significantly simplifies the electrode preparation process, shortens the electrode preparation time, and provides strong support for industrial production. The constructed energy storage system exhibits electrochemical properties such as long cycle life, high specific capacitance and high specific energy density.
[0029] Compared with the prior art, the present invention has at least the following advantages:
[0030] (1) The preparation method of the composite electrode material of the present invention is simple to operate, environmentally friendly and reliable, and the raw materials are widely available and low in cost. In addition, the method significantly simplifies the electrode preparation process, shortens the electrode preparation time, and provides strong support for industrial production.
[0031] (2) The present invention can obtain a multi-phase metal compound composite electrode material with a hierarchical multi-level structure through a simple process. On the one hand, by repeatedly in-situ depositing different active components (manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide) on the surface of the foam current collector, on the one hand, a close contact between the active material and the foam current collector is achieved, providing a good 3D conductive network for electron transmission; on the other hand, all active components can participate in the electrochemical energy storage reaction; at the same time, a hierarchical multi-level structure with a rough surface is constructed on the surface of the foam current collector, which not only provides more active sites for the electrochemical reaction, but also effectively improves the infiltration of the electrolyte and buffers the volume effect during the charge and discharge process, thereby enhancing the energy storage capacity and cycle stability of the material. Electrochemical performance tests show that at 2mA / cm 2 The discharge time under the current density is as long as 1344s, the specific capacitance value is as high as 2177F / g, and it has a good cycle life (the specific capacitance retention rate is 96% after 7000 charge and discharge cycles). The constructed electrochemical energy storage system can provide a maximum energy density of 69.8W·h / kg at a power density of 696W / kg. The composite electrode material of the present invention not only has a high specific capacitance value, but also exhibits excellent conductivity and cycle performance, can provide a high specific energy density, and is a very promising supercapacitor electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of a method for preparing a composite electrode material according to Example 1 of the present invention and application of the prepared composite electrode material in a supercapacitor;
[0033] Figure 2 The XRD analysis spectrum of the composite electrode material prepared in Example 1;
[0034] Figure 3 The SEM and TEM images of the composite electrode material prepared in Example 1;
[0035] Figure 4 This is a picture of the electrochemical test results of the composite electrode material prepared in Example 1;
[0036] Figure 5 This is a picture of the test results of a supercapacitor energy storage device made from the composite electrode material prepared in Example 1. DETAILED DESCRIPTION
[0037] The composite electrode material of the present invention is a pioneering invention. The composite electrode material of the present invention directly synthesizes the first active component (manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide) and the second active component (nickel sulfide, manganese tetraoxide and manganese sulfide) in situ multiple times on the surface of nickel foam, and the interconnected first active component nanosheet 3D network array is wrapped by the interconnected second active component amorphous sheet, forming a hierarchical multi-level structure with a rough surface. On the one hand, all active components can participate in the electrochemical energy storage reaction, and on the other hand, the hierarchical multi-level structure composed of different active components is conducive to the full contact between the electrolyte and the active substance, thereby shortening the charge transfer path and improving the reaction efficiency. The rough surface provides more active sites for the electrochemical reaction. This multi-level structure couples the comprehensive advantages of multi-component and structural functionalization, improves the electrochemical activity of the electrode, and further improves the overall structural stability of the electrode. Electrochemical performance tests show that the composite electrode material of the present invention not only has a high specific capacitance value, but also exhibits excellent conductivity and cycle performance. It is a highly potential supercapacitor electrode material. This innovation provides the possibility for industrial production and shows a good development prospect. The present invention achieves close contact between the active material and the substrate by in-situ growing the active material on the conductive substrate nickel foam, providing a good 3D conductive network for electron transmission; this method avoids the use of inactive materials such as binders and conductive agents, increases the actual content of the active material, and thus enhances the specific capacity of the electrode. The preparation method of the composite electrode material of the present invention is simple to operate, environmentally friendly and reliable, and the raw materials are widely available and low in cost. In addition, the method significantly simplifies the process flow, shortens the electrode preparation time, and provides strong support for industrial production.
[0038] In the preparation process of the composite electrode material, the reaction equation involved in the first step of the heat preservation reaction of the first reaction solution (M in the formula represents the metal ion) is as follows:
[0039] M 2+ +xF - →[MF x ] (x-2)-
[0040] CO(NH 2 ) 2 +H 2 O→2NH 3 ↑+CO 2
[0041] NH 3 +H 2 O→NH 4 + +OH -
[0042] CO 2 +H 2O→CO 3 2- +2H +
[0043] 2[NiF x ] (x-2)- +CO 3 2- +2OH - +H 2 O→Ni 2 (OH) 2 CO 3 ·H 2 O+2xF -
[0044] 5[ZnF x ] (x-2)- +2CO 3 2- +6OH - →Zn 5 (OH) 6 (CO 3 ) 2 +5xF -
[0045] [MnF x ] (x-2)- +CO 3 2- →MnCO 3 +xF -
[0046] The reaction equation involved in the second step insulation reaction of the first reaction solution is as follows:
[0047] x 2 (OH) 2 CO 3 ·H 2 O+12S 2- →2Ni x S 6 +xCO 3 2- +xH 2 O+2xOH -
[0048] Zn 5 (OH) 6 (CO 3 ) 2 +5S 2- →5ZnS+2CO 3 2- +6OH -
[0049] 7MnCO3 +O 2 +S 2- +H 2 O→2Mn 3 O 4 +MnS+7CO 2 +2OH -
[0050] The reaction equation involved in the second reaction solution heat preservation reaction (M in the formula represents a metal ion) is as follows:
[0051] CH 3 COO - +H 2 O→CH 3 COOH+OH - .
[0052] CH 3 CSNH 2 +3OH - →CH 3 COO - +NH 3 +S 2- +H 2 O
[0053] x 2+ +6S 2- →Ni x S 6
[0054] 7Mn 2+ +12OH - +S 2- +O 2 →2Mn 3 O 4 +MnS+6H 2 O.
[0055] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0056] 1. Specific embodiments of the composite electrode material and preparation method thereof of the present invention are as follows:
[0057] Example 1
[0058] The preparation method of the composite electrode material of this embodiment specifically includes the following steps:
[0059] (1) Cleaning the foam current collector:
[0060] The nickel foam current collector was ultrasonically cleaned in acetone, ethanol, and distilled water for 10 min in sequence to remove impurities and oxides on the surface of the nickel foam current collector;
[0061] (2) Preparation of nickel-zinc-manganese carbonate compound microsheet 3D network array:
[0062] A 0.05 mol / L nickel chloride solution is prepared, and zinc acetate, manganese sulfate, ammonium fluoride and urea are added, wherein the molar ratio of nickel chloride, zinc acetate, manganese sulfate, ammonium fluoride and urea is 2:1:1:4:4. After stirring evenly, a first reaction liquid is obtained, and then the first reaction liquid is transferred to a sealed Teflon reactor, and then the treated nickel foam is tilted in the reactor to make the nickel foam completely immersed in the first reaction liquid, and the materials in the reactor are heated to 120°C and then kept warm for 6 hours to complete the first step of the insulation reaction, and the reactor is naturally cooled, and the nickel foam is taken out, cleaned and dried to obtain a nickel foam coated with a nickel-zinc-manganese carbonate compound microsheet 3D network array; every 1 cm 2 The volume of the first reaction solution used for nickel foam is 5 mL;
[0063] (3) Preparation of nanosheet 3D network arrays composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide:
[0064] A 0.1 mol / L sodium sulfide aqueous solution is added to a reaction kettle, and the nickel foam coated with the nickel-zinc-manganese carbonate compound microsheet 3D network array is immersed in the sodium sulfide aqueous solution, and then the materials in the reaction kettle are heated to 130° C. and then kept warm for 7 hours to complete the second step of heat preservation reaction, and the reaction kettle is naturally cooled, and the nickel foam is taken out, washed and dried to obtain a nickel foam coated with a nanosheet 3D network array of the first active component (composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide); every 1 cm 2 The volume of sodium sulfide aqueous solution used for nickel foam coated with nickel-zinc-manganese carbonate compound microsheet 3D network array is 5 mL;
[0065] (4) Preparation of composite electrode materials
[0066] Prepare 0.05 mol / L thioacetamide aqueous solution, and add nickel acetate and manganese acetate, wherein the molar ratio of nickel acetate, manganese acetate and thioacetamide is 3:1:18, to obtain a second reaction solution. Add the second reaction solution to a sealed Teflon reactor, and then tilt the nickel foam coated with the first active component in the reactor so that the nickel foam is completely immersed in the second reaction solution, and heat the materials in the reactor to 100°C and then stand for 2 hours to allow the second active component (nickel sulfide and manganese tetraoxide) to be coated on the surface of the first active component, cool the reactor naturally, take out the nickel foam, wash and dry it, and obtain a composite electrode material; every 1cm 2 The volume of the second reaction solution used for the nickel foam coated with the first active component is 5 mL.
[0067] The preparation method of the composite electrode material of this embodiment and the schematic diagram of applying the prepared composite electrode material to a supercapacitor are shown in FIG. Figure 1 As shown, Figure 1 In the figure, Nickel foam represents nickel foam, NZM precursor represents nickel foam coated with a 3D network array of nickel-zinc-manganese carbonate compound microsheets in step (2), NZM represents nickel foam coated with a 3D network array of first active component nanosheets in step (3), NZM@NM represents the composite electrode material in step (4), Urea represents urea, TAA represents thioacetamide, and PrGO represents porous graphene.
[0068] Example 2
[0069] The preparation method of the composite electrode material of this embodiment specifically includes the following steps:
[0070] (1) Cleaning the foam current collector:
[0071] The nickel foam current collector was ultrasonically cleaned in acetone, ethanol, and distilled water for 5 min in sequence to remove impurities and oxides on the surface of the nickel foam current collector;
[0072] (2) Preparation of nickel-zinc-manganese carbonate compound microsheet 3D network array:
[0073] A 0.05 mol / L nickel chloride solution is prepared, and zinc acetate, manganese sulfate, ammonium fluoride and urea are added, wherein the molar ratio of nickel chloride, zinc acetate, manganese sulfate, ammonium fluoride and urea is 2:1:2:4:6. After stirring evenly, a first reaction liquid is obtained, and then the first reaction liquid is transferred to a sealed Teflon reactor, and then the treated nickel foam is tilted in the reactor to make the nickel foam completely immersed in the first reaction liquid, and the materials in the reactor are heated to 120°C and then kept warm for 8 hours to complete the first step of the insulation reaction, and the reactor is naturally cooled, and the nickel foam is taken out, cleaned and dried to obtain a nickel foam coated with a nickel-zinc-manganese carbonate compound microsheet 3D network array; every 1 cm 2 The volume of the first reaction solution used for nickel foam is 5 mL;
[0074] (3) Preparation of nanosheet 3D network arrays composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide:
[0075] A 0.2 mol / L sodium sulfide aqueous solution is added to a reaction kettle, and the nickel foam coated with the nickel-zinc-manganese carbonate compound microsheet 3D network array is immersed in the sodium sulfide aqueous solution, and then the materials in the reaction kettle are heated to 130° C. and then kept warm for 7 hours to complete the second step of heat preservation reaction, and the reaction kettle is naturally cooled, and the nickel foam is taken out, washed and dried to obtain a nickel foam coated with a nanosheet 3D network array of the first active component (composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide); every 1 cm 2 The volume of sodium sulfide aqueous solution used for nickel foam coated with nickel-zinc-manganese carbonate compound microsheet 3D network array is 5 mL;
[0076] (4) Preparation of composite electrode materials
[0077] Prepare 0.05 mol / L thioacetamide aqueous solution, and add nickel acetate and manganese acetate, wherein the molar ratio of nickel acetate, manganese acetate and thioacetamide is 3:1:18, to obtain a second reaction solution. Add the second reaction solution to a sealed Teflon reactor, and then tilt the nickel foam coated with the first active component in the reactor so that the nickel foam is completely immersed in the second reaction solution, and heat the materials in the reactor to 100°C and then stand for 2 hours to allow the second active component (nickel sulfide and manganese tetraoxide) to be coated on the surface of the first active component, cool the reactor naturally, take out the nickel foam, wash and dry it, and obtain a composite electrode material; every 1cm 2 The volume of the second reaction solution used for the nickel foam coated with the first active component is 5 mL.
[0078] Example 3
[0079] The preparation method of the composite electrode material of this embodiment specifically includes the following steps:
[0080] (1) Cleaning the foam current collector:
[0081] The nickel foam current collector was ultrasonically cleaned in acetone, ethanol, and distilled water for 5 min in sequence to remove impurities and oxides on the surface of the nickel foam current collector;
[0082] (2) Preparation of nickel-zinc-manganese carbonate compound microsheet 3D network array:
[0083] A 0.05 mol / L nickel chloride solution is prepared, and zinc acetate, manganese sulfate, ammonium fluoride and urea are added, wherein the molar ratio of nickel chloride, zinc acetate, manganese sulfate, ammonium fluoride and urea is 2:1:1:4:4. After stirring evenly, a first reaction liquid is obtained, and then the first reaction liquid is transferred to a sealed Teflon reactor, and then the treated nickel foam is tilted in the reactor to make the nickel foam completely immersed in the first reaction liquid, and the materials in the reactor are heated to 120°C and then kept warm for 6 hours to complete the first step of the insulation reaction, and the reactor is naturally cooled, and the nickel foam is taken out, cleaned and dried to obtain a nickel foam coated with a nickel-zinc-manganese carbonate compound microsheet 3D network array; every 1 cm 2 The volume of the first reaction solution used for nickel foam is 5 mL;
[0084] (3) Preparation of nanosheet 3D network arrays composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide:
[0085] A 0.1 mol / L sodium sulfide aqueous solution is added to a reaction kettle, and the nickel foam coated with the nickel-zinc-manganese carbonate compound microsheet 3D network array is immersed in the sodium sulfide aqueous solution, and then the materials in the reaction kettle are heated to 150° C. and then kept warm for 8 hours to complete the second step of heat preservation reaction, and the reaction kettle is naturally cooled, and the nickel foam is taken out, washed and dried to obtain a nickel foam coated with a nanosheet 3D network array of the first active component (composed of manganese tetraoxide, manganese sulfide, nickel sulfide and zinc sulfide); every 1 cm 2 The volume of sodium sulfide aqueous solution used for nickel foam coated with nickel-zinc-manganese carbonate compound microsheet 3D network array is 5 mL;
[0086] (4) Preparation of composite electrode materials
[0087] Prepare a 0.1 mol / L thioacetamide aqueous solution, and add nickel acetate and manganese acetate, wherein the molar ratio of nickel acetate, manganese acetate and thioacetamide is 3:1:20, to obtain a second reaction solution. Add the second reaction solution to a sealed Teflon reactor, and then tilt the nickel foam coated with the first active component in the reactor so that the nickel foam is completely immersed in the second reaction solution, and heat the materials in the reactor to 110°C and then stand for 2 hours to allow the second active component (nickel sulfide and manganese tetraoxide) to be coated on the surface of the first active component, cool the reactor naturally, take out the nickel foam, wash and dry it, and obtain a composite electrode material; every 1cm 2 The volume of the second reaction solution used for the nickel foam coated with the first active component is 5 mL.
[0088] 2. Specific examples of the application of the composite electrode material of the present invention as a supercapacitor electrode material are as follows:
[0089] The composite electrode material of Example 1 can be used as a supercapacitor electrode material.
[0090] Experimental example
[0091] In order to investigate the composition and appearance of the composite electrode material prepared in Example 1, the composite electrode material prepared in Example 1 was subjected to XRD analysis. The results are as follows: Figure 2 As shown; at the same time, the composite electrode material prepared in Example 1 was subjected to SEM and TEM analysis, and the results were as follows Figure 3 As shown ( Figure 3 a is the SEM image, Figure 3 b is a high-magnification SEM image. Figure 3 c is a TEM image); the composite electrode material prepared in Example 1 was subjected to electrochemical testing, and the results are as follows Figure 4 As shown, Figure 4 a is the CV cycle curve, Figure 4 b is the GCD charge and discharge curve at different current densities. Figure 4 c is the specific capacitance curve, Figure 4 d is at 20mA / cm 2 The cycle performance curve at the current density of ; The composite electrode material prepared in Example 1 is combined with a PrGO (porous graphene) negative electrode to construct an electrochemical energy storage system, and its charge storage capacity is tested. The results are as follows Figure 5 As shown, Figure 5 a is the CV cycle curve of the electrochemical energy storage system, Figure 5 b is the GCD charge and discharge curve of the electrochemical energy storage system at different current densities. Figure 5 c is the energy density and power density diagram that the electrochemical energy storage system can provide.
[0092] The method for constructing the electrochemical energy storage system is as follows: PrGO, carbon black and PVDF with a mass ratio of 7:2:1 are uniformly dispersed in N-methyl-2-pyrrolidone (N-methylpyrrolidone) reagent, ground to obtain a slurry, and then evenly coated on the surface of nickel foam (1×1 cm 2 After drying in an oven at 80°C, the composite electrode material prepared in Example 1 was used as the positive electrode, the nickel foam coated with PrGO was used as the negative electrode, and a 2 mmol / L KOH aqueous solution was used as the electrolyte to assemble an electrochemical energy storage system. PrGO was prepared according to the method in a published article (Chemical Engineering Journal 374 (2019) 347-358).
[0093] The main technical indicators of the electrochemical test of the composite electrode material prepared in Example 1 include specific capacity, charge and discharge rate, and cycle life, and the specific measurement methods are cyclic voltammetry and constant current potentiometry. The technical indicators of the electrochemical energy storage system assembled with the composite electrode material prepared in Example 1 for testing include charge and discharge rate, energy power density, and the specific measurement methods are cyclic voltammetry and constant current potentiometry.
[0094] Depend on Figure 1 It can be seen that the synthesis and preparation process of the composite electrode material and the inner layer structure of the prepared composite electrode material (3D interconnected network composed of 2D nanosheets); Figure 2 It can be seen that the composite electrode material is composed of multiple phases (manganese tetraoxide, manganese sulfide, zinc sulfide and nickel sulfide); Figure 3 (a) It can be seen that the surface layer of the composite electrode material is rough; Figure 3 (b) It can be seen that the outer layer of the composite electrode material is composed of interconnected sheet structures; Figure 3 (c) It can be seen that the second active component flakes in the composite electrode material are uniformly wrapped on the surface of the inner layer of the first active component, forming a multi-layer hierarchical structure; Figure 4 (a) and (b) show that the charge storage type of the multiphase metal compound composite material self-supporting electrode prepared in Example 1 is a Faraday cell type. Figure 4 (b) and (c) show that at 2 mA / cm 2 The discharge time is as long as 1344s at the current density, and the specific capacitance value is as high as 2177F / g. Figure 4 (d) It can be seen that the electrode has a good cycle life (the specific capacitance retention rate is 96% after 7000 charge and discharge cycles). When the composite electrode materials prepared in Examples 2 and 3 are used, the specific capacitance retention rates are 90% and 92% after 7000 charge and discharge cycles.
[0095] The electrochemical energy storage system constructed with the homemade porous graphene as the negative electrode and the composite electrode material prepared in Example 1 as the positive electrode can provide a maximum energy density of 69.8W·h / kg when the power density is 696W / kg. The electrochemical energy storage system constructed with the homemade porous graphene as the negative electrode and the composite electrode materials prepared in Examples 2 and 3 as the positive electrode can provide a maximum energy density of 48.0W·h / kg (power density of 834W / kg) and 52.7W·h / kg (power density of 831W / kg).
Claims
1. A method for preparing a composite electrode material, characterized in that: The following steps are involved: The foam collector is immersed in a first reaction solution for a first heat preservation reaction and then placed in an alkali metal sulfide solution for a second heat preservation reaction to obtain a foam collector loaded with active components. The foam collector loaded with active components is then immersed in a second reaction solution for reaction to obtain a composite electrode material; the first reaction solution is composed of nickel salt, zinc salt, manganese salt, ammonium fluoride, urea and water, and the second reaction solution is composed of nickel salt, manganese salt, thioacetamide and water.
2. The method for preparing a composite electrode material according to claim 1, characterized in that: The concentration of nickel salt in the first reaction solution is 0.05-0.1 mol / L, and the molar ratio of nickel element in nickel salt, zinc element in zinc salt, manganese element in manganese salt, ammonium fluoride and urea is 2:(1-1.05):(1-2):(4-4.05):(4-6).
3. The method for preparing a composite electrode material according to claim 1, characterized in that: The first step of heat preservation reaction is carried out at a temperature of 120-125°C for 6-8 hours.
4. The method for preparing a composite electrode material according to claim 1, characterized in that: The concentration of the alkali metal sulfide solution is 0.1-0.2 mol / L.
5. The method for preparing a composite electrode material according to claim 1, characterized in that: The second step is to keep the reaction temperature at 130-150°C for 7-8 hours.
6. The method for preparing a composite electrode material according to claim 1, characterized in that: The concentration of thioacetamide in the second reaction solution is 0.05-0.1 mol / L, and the molar ratio of nickel element in nickel salt, manganese element in manganese salt and thioacetamide is 3:(1-1.05):(18-20).
7. The method for preparing a composite electrode material according to claim 1, characterized in that: The foam current collector loaded with active components is immersed in the second reaction liquid for reaction at a temperature of 100 to 110° C. and a time of 2 to 3 hours.
8. The method for preparing a composite electrode material according to claim 1, characterized in that: The nickel salt in the first reaction solution is nickel chloride, the zinc salt is zinc acetate, and the manganese salt is manganese sulfate; the nickel salt in the second reaction solution is nickel acetate, and the manganese salt is manganese acetate; the foam collector is foam nickel; the concentration of the nickel salt in the first reaction solution is 0.05 mol / L; the temperature of the first insulation reaction is 120°C; the foam collector loaded with active components is immersed in the second reaction solution for 2 hours to react; in the first reaction solution, the molar ratio of nickel in the nickel salt, zinc in the zinc salt, manganese in the manganese salt, ammonium fluoride and urea is 2:1:(1-2):4:(4-6); in the second reaction solution, the molar ratio of nickel in the nickel salt, manganese in the manganese salt and thioacetamide is 3:1:(18-20).
9. A composite electrode material prepared by the method for preparing a composite electrode material according to any one of claims 1 to 8.
10. Use of the composite electrode material according to claim 9 as a supercapacitor electrode material.